2016
DOI: 10.1038/srep30119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver function and electroacupuncture efficacy of animals with alcoholic liver injury by the novel imaging methods

Abstract: Imaging methods to evaluate hepatic microcirculation (HM) and liver function (LF) by directly monitoring overall liver tissue remain lacking. This study establish imaging methods for LF that combines Laser speckle perfusion imaging (LSPI) and in vivo optical imaging (IVOI) technologies to investigate changes of hepatic microcirculation and reserve function in the animals gavaged with 50% ethanol (15 ml/kg·bw) for a model of acute alcoholic liver injury (ALI), and for evaluation of electroacupuncture (EA) effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“… 51 In an acute alcoholic liver-injury model, EA improved hepatic circulation and adjusted ALT and AST levels. 52 Finally, systemic inflammatory response and survival rate are significantly improved by EA in animals injected with a lethal dose of LPS. 53 Major studies on the regulation of inflammation by EA are summarized in Table 1 .…”
Section: Experimental Studies On Ea Using Pathologic Animal Modelsmentioning
confidence: 99%
“… 51 In an acute alcoholic liver-injury model, EA improved hepatic circulation and adjusted ALT and AST levels. 52 Finally, systemic inflammatory response and survival rate are significantly improved by EA in animals injected with a lethal dose of LPS. 53 Major studies on the regulation of inflammation by EA are summarized in Table 1 .…”
Section: Experimental Studies On Ea Using Pathologic Animal Modelsmentioning
confidence: 99%
“…Moreover, clinical studies have shown that adiponectin plays an active role in the pathophysiology of vascular disease in patients with NAFLD [37]. Speckle blood flow imaging technology is a new auxiliary technique for evaluating liver function [38]. In this study, the liver perfusion of the CDAA group was significantly lower than that of the normal group, and SL increased the liver perfusion.…”
mentioning
confidence: 57%
“…Inhibition of Candidalysin production can reduce the inflammatory response and thus benefit patients; (4) Acupuncture and moxibustion. Research has shown that electroacupuncture stimulation changed the levels of vasoactive substances to increase hepatic microcirculation perfusion and promote indocyanine green clearance, thereby improving hepatic microcirculation and reserve function, protecting liver function in animals with acute ALD[ 151 ]. Though the clinical application of acupuncture is widely studied, there are relatively few studies on acupuncture for ALD.…”
Section: Microbiota-gut-liver-brain Axis and Aldmentioning
confidence: 99%